If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -15 + -1x = 65 Reorder the terms: -15 + 6x + -1x = 65 Combine like terms: 6x + -1x = 5x -15 + 5x = 65 Solving -15 + 5x = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 5x = 65 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = 65 + 15 5x = 65 + 15 Combine like terms: 65 + 15 = 80 5x = 80 Divide each side by '5'. x = 16 Simplifying x = 16
| 1/5x-9/10x=10-31 | | 10=s-2 | | 7+(3)= | | 9c=50f-160 | | 16x+11=6x+231 | | 29x-34x=7-12 | | (8x+18)+(20x+4)=(6x+4) | | -4n+2=-54 | | x^2+y^2+4x+4y+8=9 | | 48-11=35x+15 | | -39+18=-5x+12x | | 3t(t+4)-3=3t(3t)+9t | | v/3-3=v/2 | | T/54=5/6 | | 3*(2-2x)=-6*(x-1) | | 3x(2-2x)=-6(x-1) | | 6x+34=-36 | | -0.7X+5.85=-0.5X+8.25 | | 4(3x-4)=2(3x+1) | | (20x+4)=(6x+4) | | 10.410= | | 3x(2-2x)=-6x(x-1) | | 2w-54=-w+21 | | 7a+4=4a | | 2=5y-3 | | H=16t^2+352t | | 15x-9=3x+2 | | (8x+18)=(6x+4) | | F=1/2gq | | 5-3s=-s-5 | | 3n-21=2n | | 8x+18=6x+4 |